Transfer from midwifery unit to obstetric unit during labour: rates, process and women's experience - Rowe, R (2011)
Background Midwifery units (MUs) provide midwife-led care for women at low risk of complications. They may be located on the same site as an obstetric unit (OU), in a hospital without obstetric services or separate from any hospital. In MUs, if unforeseen complications arise, transfer to an OU may be necessary. Aim To provide evidence to contribute to the improvement of the transfer process, help make transfer safer and less distressing for women, thereby improving the care and experience of women planning to give birth in MUs. Methods A structured literature review of existing evidence was followed by three integrated component studies using different methods. The content and quality of local NHS transfer guidelines were evaluated. Data from the Birthplace national prospective cohort study were analysed to estimate transfer rates, describe the transfer process and identify factors associated with transfer. The experiences of women transferred were explored in qualitative interviews. Findings Transfer is a common event, affecting around 25% of women planning birth in MUs, although rates in different units vary. Primiparous women are more likely to be transferred than women having a second or subsequent baby. The risk of transfer for primiparous women increases with increasing age; around 50% of women having their first baby aged 40 years or over are transferred. Local NHS transfer guidelines are generally of poor quality and pay little attention to women’s experience. Women interviewed after transfer report feeling unprepared for transfer. Sensitive care and clear communication from midwives during labour facilitate feelings of control in women and help women accept transfer as the right decision and not a 'negative' event. Transfer that is perceived by women as “too late” can have potentially serious and long-lasting negative effects. Women’s experience of the transfer journey could be improved by the offer of choice in a number of areas which would help women feel 'cared for' rather than 'transported'. Having the MU midwife continue to care for the woman after transfer should be considered 'best practice'; where this is not possible a good handover is essential. Women who have experienced transfer should be offered the opportunity to talk to a midwife about their experience.